Gambaran Self Regulated Learning di Masa Pandemi pada Mahasiswa Psikologi Universitas Medan Area - Nini Sri Wahyuni; Meri Hafni; Istiana Istiana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
During ithe ipandemic, istudents iwere iforced ito ido ionline ilearning ior ionline iin iaccordance iwith government irecommendations. iThe ipurpose iof ithis istudy iwas ito ifind iout ithe idescription iof iself-regulating ilearning iin istudents iduring ionline ilearning iduring ithe iCovid i19 ipandemic. iThis research is ia iquantitative istudy. iThe idata icollection itools iin ithis istudy iused ia iself-efficacy iscale, a parental support iscale iand ia iself-regulating ilearning iscale. iThis iresearch iuses idescriptive quantitative. iThe subjects iin ithis istudy iwere i151 isubjects. iResearchers iconducted ia iT-test iwith ia reference ito ian alpha ivalue iof i0.05 iand ilooked ifor ithe iZ iscore ifrom ithe ientire idata iobtained. The iresult iof ithis study iis ithat ifrom ia itotal iof i151 isubjects, ithere iis ia ihigh iself-regulated learning iin ifemale istudents as imany ias i55.6% iwhile iin imale istudents ias imany ias i44.4%. iIt ican be iconcluded ithat iUMA Psychology istudents ihave ihigh iself-regulated ilearning.